User-Generated Content, Electronic Word of Mouth, and Consumer Trust in Social Media Beauty Communities: A Netnographic Study - DODHY HYRONIMUS AMA LONGGY; Florentina Blandina Parapaga; Intan Farida Khasanah; Rangga Laloan (Journal of International Conference Proceedings, 2026)
Instagram has become a critical digital space for local skincare businesses to promote products, interact with consumers, and build trust through visible online communication. This study aims to explore how User-Generated Content (UGC), Electronic Word of Mouth (e-WOM), and consumer trust are constructed within Instagram-based beauty communities involving two selected local skincare stores in Merauke, South Papua, Indonesia. This study employed a qualitative design with a pure netnographic approach. Data were collected from publicly available Instagram content from January to June 2026, including feed posts, reels, captions, consumer comments, admin responses, testimonials, reposted customer stories, and highlight content. The findings show that consumer trust is constructed through two complementary patterns. ALVE tends to build informational trust through product clarity, price confirmation, promotional consistency, stock information, and admin responsiveness. Meanwhile, MIYUKI tends to build relational trust through storytelling, humor, friendly communication, Reels-based content, consumer enthusiasm, and community-oriented engagement. This study implies that local skincare stores should manage Instagram as a trust-building platform by combining accurate product information, authentic consumer participation, positive e-WOM, and emotionally engaging content.